2017
DOI: 10.1016/j.chemosphere.2017.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Sorption-desorption of selenite and selenate on Mg-Al layered double hydroxide in competition with nitrate, sulfate and phosphate

Abstract: Selenate and selenite are considered emerging contaminants and pose a risk to living organisms. Since selenium anion species are at low concentration in aquatic environments, materials for its retention are required to enable monitoring. Herein, hydrotalcite was calcined and characterised to investigate sorption and desorption of selenite and selenate in competition with nitrate, sulfate and phosphate. Sorption experiments were carried out in batch system and desorption by sequential dilution. Selenite and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…Similar phenomenon were reported for the sorption of Se(VI) by iron-oxide-coated sand [49]. The divalent charge of sulfate anions (analogous to the expected bound selenate species, SeO 4 2− ) may explain the strong competitor effect on selenate uptake (direct competitor effect or ion-exchange between sulfate and selenate anions) [50,51]. The chemical analogy between SO 4 2− and SeO 4 2− was also reported for explaining the strong impact of sulfate competitor anion on Se(VI) recovery using a polyamine weakly basic ionic exchange resin [48].…”
Section: Effect Of Coexisting Anionssupporting
confidence: 77%
“…Similar phenomenon were reported for the sorption of Se(VI) by iron-oxide-coated sand [49]. The divalent charge of sulfate anions (analogous to the expected bound selenate species, SeO 4 2− ) may explain the strong competitor effect on selenate uptake (direct competitor effect or ion-exchange between sulfate and selenate anions) [50,51]. The chemical analogy between SO 4 2− and SeO 4 2− was also reported for explaining the strong impact of sulfate competitor anion on Se(VI) recovery using a polyamine weakly basic ionic exchange resin [48].…”
Section: Effect Of Coexisting Anionssupporting
confidence: 77%
“…While some studies have shown a competition between selenate and sulfate (Constantino et al, 2017;Chubar, 2018), studies assessing the sorptive behavior of selenate and selenite in soils containing different concentrations of sulfate are still required, mainly for tropical soils. Moreover, the assessment of Se sorption at different soil layers is relevant for evaluating, among other factors, the influence of organic matter upon Se sorption capacity.…”
Section: -mentioning
confidence: 99%
“…Soil management practices that add oxyanions (e.g., phosphate and sulfate) in soils may interfere on the availability of selenate and selenite due to their competition for sorption sites (Nakamaru et al, 2006;Constantino et al, 2017). Similarly, increasing the organic matter content of tropical soils promotes an increase of net surface negative charges, hence decreasing anionic adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…SeO3 2− (Se(IV)) is presented as the dominant species, since moderate redox potential ranges and neutral pH environments are mostly met in nature [7,8]. Research on selenium removal is ongoing, with a variety of treatment methods being examined that include: chemical reduction techniques either with nanoparticles such as zero valent iron [9] and inorganic sulfur reductants such as Na2S and Na2S2O4 [10,11]; co-precipitation with barite during the crystallization phase [12]; coagulation-flocculation with Fe/Al based inorganic coagulants [13]; adsorption with inorganic adsorbents such as natural or synthesized iron-based adsorbents [14,15], apatites [16], layered double hydroxides [17], activated carbon [18], graphene oxide [19], and organic-based adsorbents such as chitosan [20] and conjugate adsorbents [21,22]; ion-exchange with resins [23]; membrane technologies [24]; bioremediation with thauera selenatis [25]; and phytoremediation using ashydrilla, duckweed, swamp lily, cattail and phragmites [26]. In order to apply the optimum water treatment process for selenium removal-apart from the removal effectiveness criteria such as the removal capacity at Ce = 10 μg/L (Q10 value), maintaining (not modification) the physicochemical characteristics of the water, and estimation of treatment cost-the water flow rate and specific requirements of treatment process should be also considered.…”
Section: Introductionmentioning
confidence: 99%